2020
DOI: 10.1016/j.stemcr.2020.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 10 Control hPSC Lines for Drug Screening in an Engineered Heart Tissue Format

Abstract: Summary Human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CM) are commercially available, and cardiac differentiation established routine. Systematic evaluation of several control hiPSC-CM is lacking. We investigated 10 different control hiPSC-CM lines and analyzed function and suitability for drug screening. Five commercial and 5 academic hPSC-CM lines were casted in engineered heart tissue (EHT) format. Spontaneous and stimulated EHT contractions were analyzed, and 7 inotropic indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 55 publications
2
39
0
Order By: Relevance
“…To vary the dosage of the applied cardiomyocyte number, we generated EHTs with different cell densities (cell-free, fibrin patches without cells; dose 1, 9×10 6 cells; dose 2, 12×10 6 cells; and dose 3, 15×10 6 cells per 1.5 mL). Because cell number influences EHT development, 17 it was not possible to only decrease cardiomyocyte number per patch. We therefore used a strategy combining cell number and patch area to create patches with different cell content.…”
Section: Methodsmentioning
confidence: 99%
“…To vary the dosage of the applied cardiomyocyte number, we generated EHTs with different cell densities (cell-free, fibrin patches without cells; dose 1, 9×10 6 cells; dose 2, 12×10 6 cells; and dose 3, 15×10 6 cells per 1.5 mL). Because cell number influences EHT development, 17 it was not possible to only decrease cardiomyocyte number per patch. We therefore used a strategy combining cell number and patch area to create patches with different cell content.…”
Section: Methodsmentioning
confidence: 99%
“…Routine assessments of hPSC-CM combine analyses at the transcript, protein, and metabolite level with phenotypic and physiological recordings [10,28,41,59,82,108]. However, neither glycan structures in general, nor the presence of a specific glycan structure at a specific glycosite within a protein, can be directly predicted from transcriptomic, proteomic, or metabolomic studies.…”
Section: Strategies To Assess Protein Glycosylationmentioning
confidence: 99%
“…One could potentially expect different responses to the drugs investigated based on racial/ethnic background as well as genetic variants (pharmacogenomics). In this context, it is noteworthy that a recent drug screening report of 10 control human pluripotent stem cell lines in an engineered heart tissue format found that, while there was great variability in baseline contractile parameters across the different lines, the variability appeared less relevant for drug screening ( Mannhardt et al., 2020 ). A number of constraints precluded us from testing every hiPSC line in our library for each of the conditions and assays.…”
Section: Discussionmentioning
confidence: 99%